Pride, Manners, and Morals Bernard Mandeville's Anatomy of Honour. - Branchi, Andrea (Brill's Studies in Intellectual History Ser., 2021)
"In Pride, Manners, and Morals: Bernard Mandeville's Anatomy of Honour, Andrea Branchi offers a reading of the Anglo-Dutch physician and thinker's philosophical project from the hitherto neglected perspective of his lifelong interest in the theme of honour. Through an examination of Mandeville's anatomy of early eighteenth-century beliefs, practices and manners in terms of motivating passions, the book traces the development of his thought on human nature and the origin of sociability. By making honour and its roots in the desire for recognition the central thread of Mandeville's theory of society, Andrea Branchi offers a unified reading of his work and highlights his relevance as a thinker far beyond the moral problem of commercial societies, opening up new perspectives in Mandeville's studies"--